ANALISIS PROYEKSI KESEMPATAN KERJA DAN PRODUKTIVITAS TENAGA KERJA DI KABUPATEN LOMBOK BARAT 2010 – 2025 - Muhammad Hendra Djunaedi (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2009)
This research takes headline about opportunity forecast analysis of activity opportunity and labour productivity in Kabupaten Lombok Barat 2010-2025. Analytical technique applied in studying this research is exponential trend analytical method depicting an movement of uptrend or downwards on a long term obtained from average of alteration from time to time and its(the value enough flattening ( smooth) From here can be suggested that, Local Government Level Of II Kabupaten Lombok Barat need determine target which must be reached that observation of developer of business field sectors capable to can be made balance to with improvement of its(the labour productivity.